BioNTech COVID-19 (BNT162b2) Vaccination and Varicella Zoster Reactivation: A Comprehensive Cross-sectional Study - Shir Azrielant; Yair Levin; Alon Peled; Liat Samuelov; Eli Sprecher; Mor Pavlovsky (Medical Journals Sweden, 2024)
Herpes zoster (HZ) results from reactivation of latent varicella-zoster virus. Recent observations have suggested that HZ is associated with vaccination against COVID-19. To investigate the association between the vaccine and HZ severity, a single-centre, cross-sectional study of all patients diagnosed with HZ and 2 control diagnoses (cellulitis and bone fractures), between 2017 and 2021, was performed. Hospital visits and hospitalization rates were compared. All medical records of patients diagnosed with HZ in the first year after the COVID-19 vaccination campaign began were reviewed, in order to generate a retrospective cohort comparing vaccinated and unvaccinated patients with HZ. All participants had received the Pfizer-BioNTech COVID-19 (BNT162b2) vaccine. During the study period, 2,413 patients were diagnosed with HZ, and when normalized to control diagnoses the number of cases remained stable. The retrospective cohort included 365 patients. A multivariate analysis controlling for sex, age, autoimmune diseases, malignancies, and immunosuppressive therapy showed higher admission rates in vaccinated compared with unvaccinated individuals (odds ratio (OR) 2.75, 95% CI 1.27-5.96, p = 0.01). However, matching techniques and stratification by age, used to better control for confounders, invalidated these findings. No differences were observed in other variables indicative of disease severity (hospital stay length and complications). In conclusion, COVID-19 vaccination was not found to be associated with an increased risk of HZ-related admission and complications.